Attention training towards positive stimuli in clinically anxious children - Waters, Allison M. (Elsevier, 2012)
OBJECTIVE: Attention bias modification training (ABMT) is a promising treatment. Nevertheless, few studies examine its effectiveness in anxious children. This study examined the efficacy of such an ABMT protocol in pediatric anxiety. METHOD: 37 anxious children were randomly assigned to one of two ABMT conditions. In the attention-towards-positive (ATP) condition, children searched 3 × 3 matrices for a happy face amongst angry faces. In the attention-training-control (ATC) condition, they searched for a bird amongst flowers. Children completed 160 trials in each of four training sessions per week for three weeks at home (1920 total trials). Clinical and attention bias measures were assessed before and after ABMT. RESULTS: Children randomized to ATP showed greater post-training attention bias towards happy faces than children randomized to ATC. ATP also produced significantly greater reductions in clinician-rated diagnostic severity and number of diagnoses, compared to ATC. In the ATP group, 50% of children who completed training did not meet criteria for their principal diagnosis, compared to 8% in the ATC group. CONCLUSION: Training anxious children to focus attention on positive features of their environment may be a promising treatment.